Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The generating function of Hermite's polynomials is given by $G(x,t)=e^{2xt-t^2}$ for $x, t \in \mathbf{R}$. It is known that $\displaystyle G(x,t)=\sum_{n=0}^\infty H_n(x) \frac{t^n}{n!}$ for $x, t \in \mathbf{R}$, where $H_n(x)=(-1)^n e^{x^2} \dfrac{d^n}{dx^n}e^{-x^2}$ for $x \in \mathbf{R}$ -is the $n$-th Hermite's polynomial. By properties of power series, for fixed $x\in \mathbf{R}$ we have that $$\frac{\partial G}{\partial t}= \sum_{n=1}^\infty \frac{\partial}{\partial t}\left[H_n(x) \frac{t^n}{n!}\right]=\sum_{n=1}^\infty H_n(x) \frac{t^{n-1}}{(n-1)!}\mbox{ for }t \in \mathbf{R}.$$

I have seen in some books that also

$$\frac{\partial G}{\partial x}= \sum_{n=0}^\infty \frac{\partial}{\partial x}\left[H_n(x) \frac{t^n}{n!}\right]= \sum_{n=0}^\infty H_n'(x) \frac{t^n}{n!} \mbox{ for }x \in \mathbf{R}.$$

I don't understand, what is the reason that we can differentiate this series with respect to $x$ (maybe series $\sum_{n=0}^\infty \frac{\partial}{\partial x} (...)$ is uniformly convergent or locally uniformly convergent, but I don't see why).


share|cite|improve this question
up vote 4 down vote accepted

We can show that we have the normal convergence of the series $f_1(x):=\sum_{n=0}^{+\infty}H_n(x)\frac{t^n}{n!}$ and $f_2(x):=\sum_{n=0}^{+\infty}H_n'(x)\frac{t^n}{n!}$ on each compact $\left[-a,a\right]$ for each $t\neq 0$ fixed (it's clear for $t=0$). Thanks to that, we can differentiate under the sum. For each $x\in\mathbb R$, we have, applying the Cauchy formula to the holomorphic function $e^{2zx-z^2}$ (for $z\in\mathbb C$, and we can extend the formula $G(x,t)=e^{2tx-t^2}$ it since these functions are equals for $t\in \mathbb R$, which is not discrete) on the circle $C(0,r), r>0$: $$\left|\frac{H_n(x)}{n!}\right|=\left|\frac 1{2\pi i}\int_{C(0,r)}\frac{e^{2xz-z^2}}{z^{n+1}}dz\right|\leq \frac 1{2\pi}\int_{C(0,r)}\frac{e^{|2xz-z^2|}}{r^{n+1}}dz\leq \frac{e^{2xr+r^2}}{r^n}.$$ Now, we fix $t\neq 0$ and we choose $r$ such that $0< r<|t|$. Then we get $$\sup_{-a\leq x\leq a}\left|H_n(x)\frac{t^n}{n!}\right|\leq \sup_{-a\leq x\leq a}\left(\frac{|t|}r\right)^ne^{2r|x|+r^2}=\left(\frac{|t|}r\right)^ne^{2ra+r^2},$$ and since $|t|<r$, the series whose general term is the RHS is convergent.

For $f_2$, note that for $n\geq 1$ we have $H_n'(x)=2nH_{n-1}(x)$, therefore $$\sup_{-a\leq x\leq a}\left|H_n'(x)\frac{t^n}{n!}\right|=2n\sup_{-a\leq x\leq a}\left|H_{n-1}(x)\frac{t^n}{n!}\right|\leq 2n\left(\frac{|t|}r\right)^ne^{2ra+r^2},$$ and the ratio test show that the series whose general terme is the RS is convergent.
And we can generalize the asked result, since by induction we get $H_{n}^{(d)}(x)=2^dn(n-1)\ldots (n-d+1)H_{n-d}(x)$ for $n\geq d$, hence a polynomial of $n$ times a Hermite polynomial, and the ratio test and the previous bound gives the normal convergence on compacts of the series $\sum_{n=0}^{+\infty}H_n^{(d)}(x)\frac{t^n}{n!}$ for all $t$.

share|cite|improve this answer
Thank you very much for answer. – Richard Sep 27 '11 at 15:14

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.